Augmented reality in science education: Bibliometric and systematic literature review of trends and outcomes - Ahmad Saputra; Insih Wilujeng; Antuni Wiyarsi; Ade Noorliza Niyamae (Universitas Muhammadiyah Malang, 2026)
Background-Augmented Reality (AR) has emerged as a prominent technology in science education; however, a comprehensive understanding of its research trends and empirical applications remains limited. Objectives-This study aims to map the research landscape and synthesize empirical evidence on the integration of AR in science education by combining bibliometric analysis and a systematic literature review. Method-A bibliometric analysis of publications indexed in the Scopus database from 2016 to 2025 was conducted using keyword-based search and screening procedures based on predefined inclusion and exclusion criteria to identify relevant studies. Additionally, a systematic review of 32 selected empirical studies was conducted to examine learning outcomes, scientific content, and methodological characteristics. Results-The findings reveal a significant increase in AR-related publications, particularly after 2020, with research focusing on conceptual understanding, motivation, and engagement across educational levels. Physics and general science dominate the subject areas, while quasi-experimental and mixed-methods designs are most commonly employed. Despite its positive impact on cognitive and affective learning outcomes, gaps remain in interdisciplinary content, teacher-focused research, and methodological diversity. Conclusions-This study highlights the growing maturity of AR research in science education while emphasizing the need for broader research scope and more diverse approaches to support future pedagogical innovation.